CIAT’s partnership with the International Fund for Agricultural Development (IFAD): guided by a shared vision - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 2016)
In line with IFAD’s strategic objective of promoting win-win arrangements and aiding smallholder agricultural producers to seize market opportunities, CIAT’s work harnesses global expertise and partnerships to highlight niche markets and make them work for the rural poor. CIAT looks forward to continuing its work with longstanding partners, including IFAD, and to shedding light on new solutions to global challenges.